Integrated water resources management: lost on the road from ambition to realisation? - Jeffrey, Paul; Gearey, Mary (IWA Publishing, 2006)
The recognition that water plays a central role in industrial, agricultural, economic, social and cultural development has, over the past half century, led to the development of strategic management approaches based on the concept of integrated water resources management (IWRM). This paper assesses the extent to which IWRM theory has been converted into practice and identifies existing “research gaps”. We set out our arguments as a critique of IWRM; describing its basic tenets, exploring its value as a conceptual tool, considering its scientific pedigree, questioning its novelty as a resource management paradigm, and suggesting ways of translating the theory into more widespread practice. Finally, we argue that whilst models in their broadest sense can make a significant contribution to IWRM research and practice, a revised assessment of the source of their value is requi